THE IMPLEMENTING OF THINK PAIR SHARE STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT FOURTH SEMESTER OF ENGLISH STUDY PROGRAM OF PROF. DR. HAZAIRIN, SH UNIVERSITY - Elva Utami (Edu-Ling: Journal of English Education and Linguistics, 2017)
ABSTRACT The research was a classroom action research. It aimed to to find out weither the implementation of Think Pair Share strategy to improve students' reading comprehension. The subjects of this research were Semester 4 students of English Study Program of Universitas Prof. Dr. Hazairin, S.H Bengkulu which consisted of five females and three males The instruments of the research were reading comprehension test, observation checklists and questionnaire. This research focused on reading comprehension. The research was conducted in two cycles that consisted of four steps in each cycle namely plan, action, observation, and reflection. The result of reading comprehension test showed that Think-Pair-Share strategy improved students’ reading comprehension students Mean score in cycle 1 is 62,9 increased to 79,2 in cycle 2.